THE IMPACT OF BULLYING ON MENTAL HEALTH IN THE FAMILY ENVIRONMENT - suryadi, suryadi suryadi (Journal of Contemporary Islamic Counselling, 2023)
This study aims to describe the impact of bullying on mental health in the family environment. Where this research was conducted on the students of the State Islamic University of Kiai Haji Achmad Siddiq Jember which is located on Jalan Mataram No. 1, Karang Miuwo, Mangli, Kaliwates District, Jember Regency through a qualitative approach with the type of case study research. The method of data collection is done by conducting interviews and direct observation. From the results of the study, the following data were obtained: (1) bullying is an act that uses power to hurt a person or group of people physically, psychologically, or verbally so that the person who is hurt gets pressure and experiences trauma. (2) someone who experiences bullying is more at risk for experiencing various psychological health problems, such as depression and trauma as well as physical health problems. (3) the factors that cause bullying (can be caused by individuals, families, or groups), the roles in bullying, and the types of bullying. (4) bullying includes actions that can cause social problems